«JUDICIAL FINDING» OF THE LEGAL NATURE OF CRYPTOCURRENCY - BARTUSIAK, PAVLO (Ehrlich’s Journal, 2023)
In the current article the legal nature and properties of the cryptocurrency phenomenon are disclosed through the analysis and comparison of the results of «judicial finding» of law that are recorded in the judicial acts. The author reveals, that judicial law of the different jurisdictions goes on the path of recognition of the bitcoin’s (and other cryptocurrencies) nature as the phenomenon that possesses the basic legal properties of money. It is established, that judges in the predominant majority use the following definitions for the characteristic of cryptocurrency: a decentralized currency; an asset that serves as a means of exchange and/or a measure of value; an anonymous digital currency; a virtual currency; an asset that serves as a means of payment; a digital production; an anonymized settlement system; a non-traditional money, etc. The author shows, that cryptocurrencies (in that sense in which they are interpreted in judicial law) have attributive properties that are inherent for the anthroposociocultural phenomena: cryptocurrencies are existentially rooted, they have a spontaneous and at the same time procedural character, they dynamically transformed into the universal phenomenon from the local phenomena, cryptocurrencies act as a natural way of self-regulation, distribution, redistribution and exchange of goods in society between its representatives, primarily in the private sector. The author substantiates the fundamental sense of the «judicial finding» of the legal nature and properties of cryptocurrency, which consists in the synthesis of the pluralistic nature of both crucial phenomena of social life – law and money: cryptocurrencies, as the phenomena that possess the qualities of money, act as the objects (subjects) of the factual life relations in which the question about the law raises. Thereby in the article it is once and again confirmed the full reliability and validity of one of the main Eugen Ehrlich’s theoretical and methodological conclusions, which he made more than a century ago – the conclusion about the poly-ontological nature of law, which is under no circumstances limited to the positive law and therefore cannot be narrowed to the positive legal norms..